Water-use strategies in two co-occurring Mediterranean evergreen oaks: surviving the summer drought - David, T. S.; Henriques, M. O.; Kurz-Besson, C.; Nunes, J.; Valente, F.; Vaz, M.; Pereira, J. S.; Siegwolf, R.; Chaves, M. M.; Gazarini, L. C.; David, J. S. (Tree Physiology, 2007)
In the Mediterranean evergreen oak woodlands of southern Portugal, the main tree species are Quercus ilex ssp. rotundifolia Lam. (holm oak) and Quercus suber L. (cork oak). We studied a savannah-type woodland where these species coexist, with the aim of better understanding the mechanisms of tree adaptation to seasonal drought. In both species, seasonal variations in transpiration and predawn leaf water potential showed a maximum in spring followed by a decline through the rainless summer and a recovery with autumn rainfall. Although the observed decrease in predawn leaf water potential in summer indicates soil water depletion, trees maintained transpiration rates above 0.7 mm day−1 during the summer drought. By that time, more than 70% of the transpired water was being taken from groundwater sources. The daily fluctuations in soil water content suggest that some root uptake of groundwater was mediated through the upper soil layers by hydraulic lift. During the dry season, Q. ilex maintained higher predawn leaf water potentials, canopy conductances and transpiration rates than Q. suber. The higher water status of Q. ilex was likely associated with their deeper root systems compared with Q. suber. Whole-tree hydraulic conductance and minimum midday leaf water potential were lower in Q. ilex, indicating that Q. ilex was more tolerant to drought than Q. suber. Overall, Q. ilex seemed to have more effective drought avoidance and drought tolerance mechanisms than Q. suber.
10.1093/treephys/27.6.79310.1093/treephys/27.6.793
Keywords: canopy conductance; groundwater; Hydraulic conductance; leaf water potential; Quercus ilex; Quercus suber; sap flow

Effects of partial defoliation on carbon and nitrogen partitioning and photosynthetic carbon uptake by two-year-old cork oak (Quercus suber) saplings - Cerasoli, S.; Scartazza, A.; Brugnoli, E.; Chaves, M. M.; Pereira, J. S. (Tree Physiology, 2004)
At the end of the growing season in late July, 20-month-old cork oak (Quercus suber L.) saplings were partially defoliated (63% of leaf area) to evaluate their ability to recover leaf area after defoliation. At 18 and 127 days after defoliation, changes in starch and nitrogen pools were determined in leaves and perennial organs, and variations in photosynthetic carbon uptake were investigated. To determine the role of stored nitrogen in regrowth after defoliation, plant nitrogen was labeled in the previous winter by enriching the nutrient solution with 15N. Plants recovered the lost leaf area in 127 days. Although there was remobilization of starch and nitrogen from leaves and perennial organs, the availability of resources for growth in the following spring was not decreased by defoliation. On the contrary, starch concentration in coarse roots was higher in defoliated saplings than in control saplings, presumably as a result of the higher net CO2 exchange rate in newly developed leaves compared with pre-existing leaves.
10.1093/treephys/24.1.8310.1093/treephys/24.1.83
Keywords: 15N labeling; defoliation; Nitrogen remobilization; starch

USE OF THERMAL IMAGING TECHNIQUES AND XANTHOPHYLLS CONTENT FOR DETERMINATION OF STRESS IN CORK OAK (QUERCUS SUBER L.) - Tronina, L.; Grant, O. M.; Ramalho, J. C.; Chaves, M. M. (ACTA PHYSIOLOGIAE PLANTARUM, 2004)
Understanding the responses of cork oak (Quercus suber L.) to actual and predicted summer conditions is essential to determine the future sustainability of cork oak woodlands in Iberia. Thermal imaging may provide a rapid method for monitoring the extent of stress. The ecophysiology of cork trees was studied over three years. Three treatments were applied by means of rainfall capture and irrigation, with plots receiving 120%, 100%, or 80% of natural precipitation. Despite stomatal closure, detected using both thermal imaging and porometry, leaf water potential fell during the summer, most drastically during the third year of accumulative stress. The quantum efficiency (ΦPSII) and the maximum efficiency Formula of photosystem II also fell more intensely over the third summer, while non-photochemical quenching (NPQ) increased. The reduced precipitation treatment sporadically further reduced leaf water potential, stomatal conductance (gs), IG (an index of gs derived from thermal imaging), ΦPSII, and Formula, and increased leaf temperature and NPQ. It is concluded that these are very resilient trees since they were only severely affected in the third year of severe drought (the third year registering 45% less rainfall than average), and removing 20% of rainfall had a limited impact.
Key words: ASKey words: ASThe following values have no corresponding Zotero field: pub-location: TIERGARTENSTRASSE 17, D-69121 HEIDELBERG, GERMANY publisher: SPRINGER HEIDELBERG
Keywords: Quercus suber L.; Stress; thermal imaging

How Plants Cope with Water Stress in the Field? Photosynthesis and Growth - Chaves, M. M.; Pereira, J. S.; MAROCO, J.; Rodrigues, M. L.; RICARDO, C. P. P.; OSÓRIO, M. L.; CARVALHO, I.; FARIA, T.; PINHEIRO, C. (Annals of Botany, 2002)
Plants are often subjected to periods of soil and atmospheric water deficit during their life cycle. The frequency of such phenomena is likely to increase in the future even outside today’s arid/semi‐arid regions. Plant responses to water scarcity are complex, involving deleterious and/or adaptive changes, and under field conditions these responses can be synergistically or antagonistically modified by the superimposition of other stresses. This complexity is illustrated using examples of woody and herbaceous species mostly from Mediterranean‐type ecosystems, with strategies ranging from drought‐avoidance, as in winter/spring annuals or in deep‐rooted perennials, to the stress resistance of sclerophylls. Differences among species that can be traced to different capacities for water acquisition, rather than to differences in metabolism at a given water status, are described. Changes in the root : shoot ratio or the temporary accumulation of reserves in the stem are accompanied by alterations in nitrogen and carbon metabolism, the fine regulation of which is still largely unknown. At the leaf level, the dissipation of excitation energy through processes other than photosynthetic C‐metabolism is an important defence mechanism under conditions of water stress and is accompanied by down‐regulation of photochemistry and, in the longer term, of carbon metabolism.
10.1093/aob/mcf10510.1093/aob/mcf105
Keywords: carbon assimilation; high temperature; Lupinus; photosynthesis; Quercus ilex; Quercus suber; stomatal functioning; Stress; Vitis vinifera; water-stress; xanthophyll cycle

Photochemical response to summer drought in Quercus ilex trees growing in a naturally CO2 enriched site - FARIA, T.; Cerasoli, S.; García-Plazaola, J. I.; Guimaraes, M. P.; Abadia, A.; Raschi, A.; Miglietta, F.; Pereira, J. S.; Chaves, M. M. (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
The effect of the interaction between water stress and growth at elevated CO2 on the leaf photochemistry were studied in Quercus ilex trees, growing in a naturally CO2 enriched site (the Bossoleto, Italy). Those plants were compared with plants growing nearby in similar soils but at ambient CO2 concentration. Our data indicate that down-regulation of photosynthesis is lower in non-watered trees from the enriched site than in non-watered trees from the ambient-CO2 site This may be associated to the higher carbon availability for the consumption of the excess absorbed light energy or to an increased protection of the photochemical apparatus against oxidative stress in plants grown under elevated CO2.
The following values have no corresponding Zotero field: periodical: IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS pub-location: PO BOX 17, 3300 AA DORDRECHT, NETHERLANDS
Keywords: Elevated CO2; fluorescence; water stress; xanthophylls

Seasonal changes in xanthophyll composition and photosynthesis of cork oak (Quercus suber L.) leaves under mediterranean climate - García-Plazaola, J. I.; FARIA, T.; Abadía, J.; Chaves, M. M.; Pereira, J. S. (Journal of Experimental Botany, 1997)
Seasonal changes in pigment composition of sun and shade leaves of cork oak (Quercus suber) were studied under field conditions in Portugal. Expanding leaves showed a high concentration of xanthophyll cycle components, violaxanthin, antheraxanthin and zeaxanthin. The pool of violaxanthin plus antheraxanthin plus zeaxanthin (V+A+Z) varied greatly between the seasons, being higher at the end of summer and in winter when photosynthesis was limited by water stress and cold, respectively. The size of V+A+Z pool was associated to synthesis of zeaxanthin in response to an excess of light. In sun leaves, midday A+Z relative content was positively correlated with the V+A+Z pool, whereas in shade leaves A+Z decreased with leaf ageing. In both leaf types A+Z was positively correlated with the non-photochemical quenching (NPQ) of chlorophyll a fluorescence. However, in winter NPQ did not change significantly throughout the day, whereas the (A+Z)/(V+A+Z) increased following the typical daily trend observed in other seasons.
10.1093/jxb/48.9.166710.1093/jxb/48.9.1667
Keywords: chlorophyll fluorescence; pigments; Quercus suber; thermal dissipation; xanthophylls

Growth at elevated CO2 leads to down-regulation of photosynthesis and altered response to high temperature in Quercus suber L. seedlings - FARIA, T.; Wilkins, D.; Besford, R. T.; Vaz, M.; Pereira, J. S.; Chaves, M. M. (Journal of Experimental Botany, 1996)
The effects of growth at elevated CO2 on the response to high temperatures in terms of carbon assimilation (net photosynthesis, stomatal conductance, amount and activity of Rubisco, and concentrations of total soluble sugars and starch) and of photochemistry (for example, the efficiency of excitation energy captured by open photosystem II reaction centres) were studied in cork oak (Quercus suber L.). Plants grown in elevated CO2 (700 ppm) showed a down-regulation of photosynthesis and had lower amounts and activity of Rubisco than plants grown at ambient CO2 (350 ppm), after 14 months in the greenhouse. At that time plants were subjected to a heat-shock treatment (4 h at 45°C in a chamber with 80% relative humidity and 800–1000 µmol m−2 s−1 photon flux density). Growth in a CO2-enriched atmosphere seems to protect cork oak leaves from the short-term effects of high temperature. Elevated CO2 plants had positive net carbon uptake rates during the heat shock treatment whereas plants grown at ambient CO2 showed negative rates. Moreover, recovery was faster in high CO2-grown plants which, after 30 min at 25°C, exhibited higher net carbon uptake rates and lower decreases in photosynthetic capacity (Amax as well as in the efficiency of excitation energy captured by open photosystem II reaction centres (FvJFm than plants grown at ambient CO2. The stomata of elevated CO2 plants were also less responsive when exposed to high temperature.
10.1093/jxb/47.11.175510.1093/jxb/47.11.1755
Keywords: acclimation; Elevated CO2; photo- synthesis; Quercus suber L.; Temperature

Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M. M.; Pereira, J. S.; Cerasoli, S.; CliftonBrown, J.; Miglietta, F.; Raschi, A.; Chaves J. S. ;Cerasoli, S. ;Clifton Brown (JOURNAL OF BIOGEOGRAPHY, 1995)
A marginal improvement in the response of Quercus ilex adult trees to drought appears to occur under a long-term natural CO2 enrichment. This is expressed, for example, by the absence of midday stomatal closure in trees growing under elevated CO2. Some protection against high irradiance and high temperature seems also to occur at the photochemical level, presumably as a result of more carbon available to the consumption of excess light energy. This would allow a better performance of the plants grown under elevated CO2 during the warmer hours of the day and therefore playing an important adaptation role under drought conditions. A marginal increase in the concentration of soluble sugars and starch was observed in the leaves of trees growing at elevated CO2 as compared with plants at ambient CO2, mainly during the midday hours. We may speculate that this will be advantageous both in terms of carbohydrate reserves for growth (e.g. more roots) and osmotic adjustment.
From Duplicate 2 (Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M M; Pereira, J S; Cerasoli, S; CliftonBrown, J; Miglietta, F; Raschi, A)From Duplicate 2 (Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M M; Pereira, J S; Cerasoli, S; CliftonBrown, J; Miglietta, F; Raschi, A)The following values have no corresponding Zotero field: pub-location: OSNEY MEAD, OXFORD, OXON, ENGLAND OX2 0EL publisher: BLACKWELL SCIENCE LTD label: Fisiologia - CO2 elevado
Keywords: Elevated CO2; Fisiologia - CO2 elevado; fluorescence; long-term acclimation; stomata; sugars; water deficits